Inclusive model through the use of ICT in attention to indigenous students of higher education - Valenzuela, Blanca Aurelia (Consorcio de Universidades Mexicanas A.C., 2020)
The inclusion of indigenous students represents a challenge in the permanence in Higher Education, so the use of ICT is a means that facilitates such process with ubiquitous learning. Therefore, the general objective of this research is to describe the process of inclusion of indigenous students and the use of ICT in higher education in Sonora, Mexico in order to determine an inclusive model of care. A descriptive-correlative quantitative study was carried out with a non-experimental transectional design, the mobile devices questionnaire on education was applied as a data collection technique: ubiquitous learning (Sevillano, 2016) and the Inclusion Index (Both & Ainscow, 2000) to 84 university students from an indigenous ethnic group in Sonora, Mexico. For the data analysis the statistics program SPSS version 21 and EQS 6.1 were used. The results indicate the use of the Smartphone and laptop for academic and social purposes more frequently; in the inclusion process, the need to design classes that address the educational needs and employment of the use of ICT by teachers, as well as the promotion of an inclusive culture. The structural model explains 32% the educational inclusion. It is proposed to implement the model and measure the impact on the academic-social achievement of indigenous students. Keywords: higher education, indigenous students, educational inclusion, information and communication technologies (ICT).